Symptoms of stress among student-athletes of Universiti Teknologi MARA (UiTM) Malaysia - Parnabas, Vincent; Mahamood, Yahaya; Parnabas, Julinamary; Ismail, Sarimah; Abdullah, Nagoor Meera; Abd Rahim, Mohd Rahizam (SCIENCEDOMAIN international, 2014)
Background of the Study: Recent evidence suggests that student-athletes may experience greater levels of stress or anxiety due to the dual demands of athletics and academics expectation placed on them.A lot of pressure is placed on collegiate athletes to achieve excellence in academics and sports.The symptoms of stress are known as physiological, behavioral, cognitive and emotional.Aims: The main purpose of this study was to examine the symptoms of stress among student-athletes who compete at differing levels in Malaysia.Study Design: Comparative descriptive study design was used to compare the symptoms of stress among athletes.Place and Duration of Study: Sample: The participants of this study were recruited from student-athletes of Sport Science and Recreation Faculty, Universiti Teknologi MARA (UiTM), Malaysia.Methodology: The sample consisted of 152 athletes, with national (N=41), state (N=33), district (N=37) and university (N= 41) level athletes.Based on this sample, there are 80 male and 72 female student-athletes. The student athletes voluntarily participated in the study and they were randomly selected during a sport event.The instrument used for the study comprised of a 28-item Symptoms of Stress, which include Physiological symptoms, Behavioral Symptoms, Cognitive Symptoms and Emotional Symptoms.Results: The results showed that university level athletes exhibited higher levels of physiological and cognitive stress than other categories of athletes.The result also showed that the national level athletes exhibited higher level of behavioral symptoms of stress. Conclusion: The findings of this research determined that there are differences in the symptoms of stress, showed by different categories of Malaysian athletes.Sport psychologists, sport counselors and coaches should use the present findings to recommend cognitive and physiological coping strategies to university athletes and behavioral strategies to national level athletes, while dealing with their stress.